2016
DOI: 10.1016/j.neuron.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Dependent Regulation of Distinct Transport and Cytoskeletal Remodeling Functions of the Dendritic Kinesin KIF21B

Abstract: Summary The dendritic arbor is subject to continual activity-dependent remodeling, requiring a balance between directed cargo trafficking and dynamic restructuring of the underlying microtubule tracks. How cytoskeletal components are able to dynamically regulate these processes to maintain this balance remains largely unknown. By combining single molecule assays and live imaging in rat hippocampal neurons, we have identified the kinesin-4 KIF21B as a molecular regulator of activity-dependent trafficking and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
147
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(169 citation statements)
references
References 57 publications
22
147
0
Order By: Relevance
“…Analysis of fluorescence intensity of single KIF21B-MD-CC1-GFP molecules in comparison to monomeric GFP and dimeric EB3-GFP indicated that they were dimers, as expected (Figure 2A, Supplementary file 2). This conclusion was confirmed by two-step photobleaching profiles (Figure 2B) and was in agreement with the published data obtained in HeLa cell lysates with a similar construct (Ghiretti et al, 2016).
10.7554/eLife.24746.006Figure 2.Dimeric motor domain of KIF21B slows down MT polymerization in vitro.( A ) Histograms of fluorescence intensities at the initial moment of observation of single molecules of the indicated proteins immobilized on coverslips (symbols) and the corresponding fits with lognormal distributions (lines).
…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Analysis of fluorescence intensity of single KIF21B-MD-CC1-GFP molecules in comparison to monomeric GFP and dimeric EB3-GFP indicated that they were dimers, as expected (Figure 2A, Supplementary file 2). This conclusion was confirmed by two-step photobleaching profiles (Figure 2B) and was in agreement with the published data obtained in HeLa cell lysates with a similar construct (Ghiretti et al, 2016).
10.7554/eLife.24746.006Figure 2.Dimeric motor domain of KIF21B slows down MT polymerization in vitro.( A ) Histograms of fluorescence intensities at the initial moment of observation of single molecules of the indicated proteins immobilized on coverslips (symbols) and the corresponding fits with lognormal distributions (lines).
…”
Section: Resultssupporting
confidence: 93%
“…Unlike its paralogue KIF21A, which is largely diffuse when expressed in similar conditions (van der Vaart et al, 2013), KIF21B bound to MTs and accumulated at their ends at the cell periphery (Figure 1A). Live cell imaging showed that KIF21B processively moves along MTs with an average speed of 0.63 ± 0.22 µm/s (mean±SD) (Figure 1B); this velocity is three times faster than that recently described for HaloTag-labeled KIF21B in neurons (Ghiretti et al, 2016). In internal cell regions, where no clear accumulation of the motor at growing MT ends was observed, the expression of KIF21B led to a ~1.5 fold reduction in the MT growth rate measured with the MT plus-end marker EB3-TagRFP-T (Stepanova et al, 2003; van der Vaart et al, 2013) (Figure 1C).…”
Section: Resultssupporting
confidence: 47%
See 3 more Smart Citations